2017
DOI: 10.1002/gps.4662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding whole‐body vibration to routine day activity program on physical functioning in elderly with mild or moderate dementia: a randomized controlled trial

Abstract: Objective: To evaluate the effects of whole-body vibration (WBV) added to a routine activity program on lower limb strength, balance, and mobility among community-dwelling individuals with mild or moderate dementia, compared with the routine program alone. Methods: Fifty-four older adults (40 women; mean (SD) age: 79.8 (6.1) years) with mild or moderate dementia were recruited from two daycare centers. The participants were randomly allocated to undergo a routine day activity program combined with WBV training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 41 publications
2
59
0
1
Order By: Relevance
“…Nineteen studies investigated the effect of exercise programs on gait (Table ). All except 2 were RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nineteen studies investigated the effect of exercise programs on gait (Table ). All except 2 were RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Control groups received usual treatment (13 studies), motor placebo activity (2 studies), group‐based social activities (2 studies), supervised group walking (1 study), and a home safety assessment (1 study). Six studies had low risk of bias; most had low to moderate risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, among older individuals, a number of studies observed WBV-induced improvements in lower limb blood flow [15,16] and body balance [17,18]. On the other hand, other studies could not reveal such beneficial effects from exposure to WBV on peripheral circulation [19] or body balance [20][21][22]. Also, widely variable study protocols among the investigators complicate the interpretation of the available study results.…”
Section: Introductionmentioning
confidence: 99%
“…Die erhobenen kardiovaskulären Parameter der untersuchten Senioren liegen, von wenigen Ausnahmen abgesehen, im alterstypischen Normbereich. Sollte sich zeigen, dass sich die kardiovaskulären Parameter durch die Intervention verbessern lassen, wie es zahlreiche Studien nahelegen, könnte sich dieser Effekt durch eine besseren Durchblutung des Gehirns auch positiv auf Prognose und Verlauf der Demenz auswirken [11] [12][13] [14].…”
Section: Fazit Für Die Praxisunclassified